(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines moral ideals as abstract images of a person who embodies the highest moral qualities. Their role in shaping ideas about moral perfection, defining guidelines for personal development and achieving moral completeness and harmony is emphasized. It is noted that moral ideals serve not only as a guide for individual development, but also as an important guiding principle for society as a whole. Particular attention is paid to the fact that without defining and implementing a national idea based on traditional moral values, the spiritual foundations of the people and global experience, without a clear strategy and consistent transition to long-term development, it is impossible to ensure comprehensive and sustainable progress.